Simulation of the New Product Development Process for Performance Improvement - Bhuiyan, Nadia; Gerwin, Donald; Thomson, Vince (Management Science, 2004)
This paper explores the linkages between key features of the new product development (NPD) process and NPD performance and suggests ways of designing the process to improve performance. Using a stochastic computer model, we examine, under varying uncertainty conditions, how the key features of overlapping and functional interaction affect the performance measures of development time and effort (total person-days for a project). Findings indicate that, first and foremost, whether or not overlapping occurs, increasing functional interaction eventually leads to a trade-off between development time and effort. Second, an “early-start-in-the-dark” approach of increasing overlapping with no functional interaction is inferior even to an “over-the-wall” approach. Third, increasing overlapping when some functional interaction exists is beneficial in low uncertainty and harmful in high uncertainty. Fourth, concurrent engineering (CE) is appropriate under low uncertainty, while a type of sequential engineering (SE), different than the “over-the-wall” approach, should be used under high uncertainty, and last, dedicated teams are suitable under high, and not low, uncertainty. We developed the model with the aid of a company and validated it against a published account of five case studies.